Tuning gradient microstructures in immiscible polymer blends by viscosity ratio. Issue 44 (24th June 2019) - Pan, Dan; Hufenus, Rudolf; Qin, Zongyi; Chen, Long; Gooneie, Ali
ABSTRACT: Bioinspired gradient microstructures provide an attractive template for functional materials with tailored properties. In this study, filaments with gradient microstructures are developed by melt‐spinning of immiscible polymer blends. The distribution of the gradient morphology is shown to be controlled by the viscosity ratio of polymers as well as the geometry of the capillary die. Distinct microstructure gradients with long thin fibrils near the surface region and short large droplets near the center region of the filament, as well as the inverse pattern, are formed in systems with different viscosity ratios. The shear flow field in the capillary can elucidate the formation mechanisms of gradient morphologies during processing. The results demonstrate how the features of a gradient microstructure can be tailored by the design of capillary geometry and processing conditions. The viscosity ratio is then introduced as an adjusting tool to control the gradient morphology in a given processing setup. In consequence, this study provides novel design routes for achieving gradient morphologies in immiscible polymers. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48165. Abstract : Gradient morphologies can be developed by melt‐spinning of polymer blends.